DESIGNING ENGLISH MATERIALS BY USING TAPAK TUAN FOLKLORE - Ichsan Darmawan; Saut Gultom; Maranata Lumban Batu; Yenita Sembiring (elt, 2022)
Tapaktuan is not only famous for its natural beauty but also because of many folklores that grew from this city, like a disobedient child who is said to be almost similar to Malin Kundang's story, but this story has a version from Tapaktuan City, and the most famous is the story of a dragon and a very powerful master. The majority of livelihoods in Tapaktuan are nutmeg farmers, rice fields and fishermen. The unique thing is that the economy is very rich in natural resources but the people there are not rich. Because it is said that their ancestors once said